31. Internet Audio Products (3/3) - Schwartz, Linda; de Schutter, Adrienne; Fahrni, Patricia; Rudolph, Jim (International Review of Research in Open and Distributed Learning, 2004)
Two contrasting additions to the online audio market are reviewed: iVocalize, a browser-based audio-conferencing software, and Skype, a PC-to-PC Internet telephone tool. These products are selected for review on the basis of their success in gaining rapid popular attention and usage during 2003-04. The iVocalize review emphasizes the product’s role in the development of a series of successful online audio communities – notably several serving visually impaired users. The Skype review stresses the ease with which the product may be used for simultaneous PC-to-PC communication among up to five users.